Characterization and environmental interpretation of a floodplain Holocene paleosoil: Implications for paleohydrological reconstructions in the Upper Paraná River, Brazil - Stevaux, José C.; Barczysczyn, Olga [UNESP]; Medeanic, Svetlana; de Nóbrega, Maria Teresa (My University, 2006)
Alluvial paleosoil horizons from the 3 to 4 m high banks of the Paraná River were used to reconstruct the palaeoenvironmental history and palaeohydrological regime of the river. The bank consists of a Middle to Late Holocene sequence of sandy to silty clay layers of overbank deposits. The paleosoil horizon is located to a depth of 1.95 m from the top of the bank and is recognized as a guide horizon throughout the floodplain of the Upper Paraná River floodplain. Analyses of organic matter (δ13C and humic/fulvic acids), palynology (pollen and charcoal fragments), magnetic susceptibility, micromorphology, x-ray diffraction and 14C dating were conducted for samples from two representative profiles of the study area. Two phases were characterized in the history of the river: 1) An older phase, of stability in fluvial hydrology (stasis) with low frequency of floods, which produced conditions for soil development (14C 1700 ± 70 yr. BP). At this period, the predominance of herbaceous vegetation (determinated by pollen and δ13C analyses) suggests a climate less humid than the present one, and 2) A second phase, when climate changed to the present conditions of humidity (annual rain fall of 1600 rum) and characterized by the predominance of C3 plants. Under this new hydrological regime, the river developed an agradational floodplain, with a depositional sedimentary rate of 1.2 mm.y-1. © 2006 Gebrüder Borntraeger.
Keywords: floodplain; Holocene; magnetic susceptibility; paleoenvironment; paleohydrology; paleosol; palynology; Parana River; South America